(untitled) (The Journal of Plant Protection Sciences, 2020)
A field investigation was conducted for two consecutive years of 2003-04 and 2004-05 at Adisaptagram Block Seed Farm, Hoogly, West Bengal to find out the incidence pattern and population dynamics of aphids on various potato germplasms. The common potato germplasms viz Kufri Chandramukhi, Kufri Jyoti, Kufri Jawhar along with three processing varieties like Kufri Chipsona-1, Kufri Chipsona 2 and Atlantic were screened against aphids.